Class, union, or party allegiance? Comparing pension reform preferences in Britain and Germany - Ebbinghaus, B; Naumann, E (Palgrave Macmillan, 2017)
This chapter explores to what degree public opinion, particularly specific social groups including social classes, retirees, members of trade unions, and supporters of political parties, defend the status quo or are willing to support reforms. It distinguishes two major dimensions of pension-specific attitudes, retrenchment and redistribution. Using data from the 2008 European Social Survey, the study compares two countries with different pension systems, organized interests, and party systems: Britain and Germany. Our results show pronounced cross-national differences in attitudes towards the redistributive character of the pensions system but less variation with regard to retrenchment of pension benefits. Political affiliations show also more variation than social classes, indicating that ideological alignment is more pronounced than social class.